Using the live assessment to discriminate between Autism Spectrum Disorder and Disinhibited Social Engagement Disorder. (March 2023) - Davidson, Claire; Turner, Fiona; Gillberg, Christopher; Campbell, Sharon.L.; Boyd, Sheila; Minnis, Helen
Abstract: Background: Children with Autism Spectrum Disorder (ASD) and children with Disinhibited Social Engagement Disorder (DSED) may present with similar social problems, despite differing aetiologies, resulting in diagnostic conundrums. Methods: Thirty children: 10 with ASD, no maltreatment history, 10 with DSED and 10 typically developing children were assessed via 'gold standard' ASD assessments, including the Autism Diagnostic Observational Schedule (ADOS) and a unique unstructured observation known as the Live assessment. Live utilises a triadic interaction (2 assessors and child), playful teasing and social 'stress' scenarios to increase the social challenge. Results: The ADOS supported discrimination of DSED from ASD to a degree. Where additional neurodevelopmental problems created ambiguity, the Live assessment was more supportive than the ADOS for unpicking the underlying nature of the social problems. Conclusion: Live supported differentiation between ASD, DSED and other neurodevelopmental problems. The greater social challenge presented by Live exacerbated core problems of ASD and, in DSED, core social skills stood out. Highlights: Socially challenging unstructured observation can help discriminate between ASD and DSED Core communication, interaction and imagination skills were found in DSED and not ASD. Neurodevelopmental overlap in DSED, as well as ASD, should be expected. Social problems related to ADHD can be easier unpicked in an unstructured, free-flowing assessment.